After development : transformation of the Korean presidency and bureaucracy - Ham, Sŏng-dŭk (Georgetown University Press, 1997)
This book explores the dynamic changes now taking place in the South Korean government as a result of recent social and economic liberalization. Sung Deuk Hahm and L. Christopher Plein trace the emergence in Korea of a post-developmental state, in which both increasingly autonomous capital interests and growing public expectations of a higher quality of life challenge existing authoritarian institutions. Separating out the constituent parts of the Korean state, they then explore the evolving roles of the Korean presidency and bureaucracy in setting national policy.